A hyper-cross-linked polymer derived from pitch as an efficient adsorbent for VOCs. (October 2022) - Liu, Huan; Liu, Zi-Xin; Yu, Hao-Ran; Wang, Yan; Zhao, Feng-yun; Wang, Jian-ying
Hyper-cross-linked polymers (HCPs) have been attracted widespread attention as adsorbents in recent years. A series of HCPs (HCP-1, HCP-2 and HCP-3) were synthesized via a Friedel-Crafts reaction using low-cross-linked pitch as precursor and dichloromethane (DCM) as cross-linking reagent and solvent. The prepared HCPs were characterized by N2 adsorption, Fourier transform infrared (FI-IR), Scanning electron microscopy (SEM), Thermogravimetric analysis (TGA) and static water contact angle. The resultant HCPs possess micro/meso pore structures and a high stability. The Brunauer-Emmett-Teller (BET) surface areas of HCP-1, HCP-2 and HCP-3 are 152 m 2 ·g −1, 467 m 2 ·g −1 and 447 m 2 ·g −1, respectively. Their total pore volumes vary from 0.207 cm·g −1 to 0.545 cm 3 ·g −1 and following the sequence of HCP-1<HCP-3<HCP-2. The FTIR spectra of HCPs suggests the DCM is successfully grafted onto the skeleton structure. Dynamic adsorption capacities of the prepared HCP-1, HCP-2 and HCP-3 were examined and the results show the adsorption properties of o-xylene on HCP-2 are significantly higher than that of the other HCPs. The adsorption amount of o-xylene on HCP-2 is 198.18 mg·g −1, which is higher than that of benzene, suggesting a strong adsorption selectivity for o-xylene over benzene. In addition, the effect of water vapor on the adsorption of o-xylene onto HCP-2 was investigated. The dynamic adsorption amount of o-xylene on HCP-2 decreases by 76.47% under the relative humidity (RH) of 30%, implying that the HCP-2 has poor hydrophobicity. The equilibrium adsorption capacity of o-xylene on HCP-2 shows a slight decline after five adsorption cycles.